Effectiveness Test of Green Betel Leaf Extract (Piper betle L.) on the Growth of Staphylococcus aureus - Riris Grace Aprilia; Yohania Premita; Boyke Marthin Simbolon; Riyani Susan Bt. Hasan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Diseases due to infection where one of the causes is Staphylococcus aureus is one of the biggest problems faced today. Treatment using penicillin antibiotics tends to cause resistance and side effects, so people prefer to overcome them by means of self-medication or the use of traditional ingredients such as betel leaf. The purpose of the study was to examine the effect of green betel leaf extract (Piper betle L.) on the growth of Staphylococcus aureus on the antibacterial activity. Methods: This study is experimental research in vitro using a well diffusion method. The betel leaf was extracted using the maceration method and made into concentrations of 5%, 10%, 15%, and 20%. Results: The average diameter of the inhibition zones was 9.82 mm, 9.11 mm, 9.28 mm, and 9.01 mm at concentrations of 5%, 10%, 15%, and 20%, sequentially. Conclusion: The antibacterial activity of betel leaf extract in the overall concentration and the most optimal concentration was 5% at 9.82 mm.